57 The low dose colchicine after myocardial infarction (LoDoCo-MI) study: a pilot randomised placebo controlled trial of colchicine following myocardial infarction. (16th October 2019) - Hennessy, T; Soh, L; Bowman, M; Kurup, R; Schultx, C; Hillis, GS
Abstract : Background: Following an acute myocardial infarction (MI), patients with persistently elevated biomarkers of inflammation, in particular C-reactive protein, are at significantly increased risk of further adverse cardiovascular events. Colchicine is a unique anti-inflammatory medication that has shown promise in reducing such events in patients with stable coronary heart disease. The current study tested the ability of low dose colchicine to reduce CRP levels at 30-days after an acute MI, a key marker of future outcome, and its safety and tolerability in this setting. Methods: We conducted a randomised, double-blind, trial of low-dose colchicine (0.5 mg daily) or matching placebo in 237 patients admitted with an acute MI. The primary end-point was the proportion of patients with a residual CRP level ≥2 mg/L after 30 days of treatment, a threshold associated with a worse prognosis. (Figure 1 ). Results: At 30-day follow-up, 44% of patients treated with colchicine had a hsCRP level ≥2 mg/L compared to 50% of those randomised to placebo (p=0.35) and the median hsCRP in patients randomised to colchicine was 1.6 mg/L (interquartile range [IQR] 0.7–3.5) compared to 2.0 mg/L (IQR 0.9–4.0) in patients randomised to placebo (p=0.11). The median absolute reduction in hsCRP levels was -4.3 mg/L (IQR -1.1 to -14.1) among colchicine treated patients and -3.3 mg/L (IQR -0.9 to -14.4, p=0.44) in placebo treated patients. (Figure 2 ). The relative reduction was a fall of 78% compared to a fall of 64% (p=0.09). Low dose colchicine was well tolerated and did not reduce compliance with other secondary preventative medications at 30-days. Conclusion: Treatment with low dose colchicine was safe and well tolerated, but was not associated with a significantly increased likelihood of achieving a CRP level <2 mg/L or lower absolute levels of CRP 30 days after an acute MI; beneficial trends were, however, observed and treatment was safe and well-tolerated. A large-scale outcome trial is required and these data suggest this will be safe and feasible. We believe, therefore, that the totality of evidence supports the need for a large scale outcome trial in patients with recent MI. Importantly in this regard the current study demonstrates the safety and tolerability of low dose colchicine after acute MI.